Disability after severe head injury: observations on the use of the Glasgow Outcome Scale. Issue 4 (April 1981) - Jennett, B; Snoek, J; Bond, M R; Brooks, N
Abstract : The nature of the neurological and mental disabilities resulting from severe head injuries are analysed in 150 patients. Mental handicap contributed more significantly to overall social disability than did neurological deficits. This social handicap is readily described by the Glasgow Outcome Scale, an extended version of which is described and compared with alternatives. Comments are made about the quality of life in disabled survivors.